Identification of a RelA/SpoT Homolog and Its Possible Role in the Accumulation of Astaxanthin in Haematococcus pluvialis - Jin, Hui; Lao, Yong Min; Zhou, Jin; Cai, Zhong Hua (Frontiers in Plant Science, 2022)
A RelA/SpoT homolog, HpRSH, was identified in Haematococcus pluvialis. HpRSH was found to catalyze Mg2+-dependent guanosine tetraphosphate (ppGpp) synthesis and Mn2+-dependent ppGpp hydrolysis, respectively. The transcription of HpRSH was significantly upregulated by environmental stresses, such as darkness, high light, nitrogen limitation, and salinity stress. The intracellular ppGpp level was also increased when exposed to these stresses. In addition, the classical initiator of stringent response, serine hydroxamate (SHX), was found to upregulate the transcription of HpRSH and increase the level of ppGpp. Moreover, stringent response induced by SHX or environmental stresses was proven to induce the accumulation of astaxanthin. These results indicated that stringent response regulatory system involved in the regulation of astaxanthin biosynthesis in H. pluvialis. Furthermore, stringent response was unable to induce astaxanthin accumulation under dark condition. This result implied that stringent response may regulate astaxanthin biosynthesis in a light-dependent manner.